Detection of Ampicillin Resistance Encoding Gene of Escherichia coli from Chickens in Bandung and Purwakarta - Kuntum Khoirani; Agustin Indrawati; Surachmi Setiyaningsih (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
The purpose of this study was to test the resistance and to detect antibiotic resistence encoding gene in E. coli bacteria from chickens in Bandung and Purwakarta livestock. 18 E. coli isolates were tested for antibiotics resistance using the disk diffusion method. Isolates that were categorized as resistant and intermediate to antibiotics, then polymerase chain reaction was utilized to detect the resistent coding gene. The test results showed that all E. coli isolates from chickens in Bandung and Purwakarta were resistant to ampicillin (100%). E. coli isolates were still sensitive to chloramphenicol (11.1%) and gentamicin (22.2%). The gene encoding for ampC resistance from the test were in the amount of 77.7%. Sensitivity test results and detection of resistance coding gene showed that almost all isolates were resistant to ampicillin antibiotics and E. coli isolates were still sensitive to chlorampenicol and gentamicin.